Cryptic Species Diversification of the Pedicularis siphonantha Complex (Orobanchaceae) in the Mountains of Southwest China Since the Pliocene - Liu, Rong; Wang, Hong; Yang, Jun-Bo; Corlett, Richard T.; Randle, Christopher P.; Li, De-Zhu; Yu, Wen-Bin (Frontiers in Plant Science, 2022)
Morphological approaches often fail to delimit species in recently derived species complexes. This can be exacerbated in historical collections which may have lost key features in specimen preparation and preservation. Here, we examine the Pedicularis siphonantha complex, endemic to the Mountains of Southwest China. This complex is characterized by its red/purple/pink and long-tubular corolla, and twisted, beaked galea. However, herbarium specimens are often difficult to identify to species. Molecular approaches using nrITS or nrITS+ptDNA have been successfully used for species identification in Pedicularis. To resolve taxonomic confusion in the P. siphonantha complex, we reconstructed phylogenies of the complex using nrITS and four plastid DNA loci (matK, rbcL, trnH-psbA, and trnL-F). To recover as much of the phylogenetic history as possible, we sampled individuals at the population level. Topological incongruence between nrITS and ptDNA was recovered in clades including two widely distributed species, P. milliana and P. tenuituba. Based on morphological, geographical, and genetic evidence, we suggest that hybridization/introgression has occurred between P. milliana and P. sigmoidea/Pedicularis sp. 1 in the Yulong Snow Mountain of Lijiang, northwest Yunnan, and between P. tenuituba and P. dolichosiphon in Yongning of Ninglang, northwest Yunnan. After removing conflicting DNA regions in P. dolichosiphon (nrITS) and P. milliana (ptDNA), the concatenated nrITS and ptDNA phylogenies distinguish 11 species in the P. siphonantha complex, including two undescribed species, from the Jiaozi and Yulong Snow Mountains, respectively. Phylogeographical analyses indicate that the P. siphonantha complex originated south of the Hengduan Mountains, expanding north to the Himalayas and the Yunnan-Guizhou Plateau. Moreover, uplift of the Qinghai-Tibet Plateau and climate oscillations may have driven further diversification in the complex.